Father-daughter relationships during girls’ adolescence in urban China - Qiong Xu (Educate~, 2009)
Contextualization

Contemporary Chinese families are experiencing tremendous changes, with the adoption of economic reform and the implementation of the one-child-per-family policy. These changes are inevitably leading to changing parent-child relationships in families, especially for girls’ relationships with their parents. The paper is to research girls’ and fathers’ perceptions of father-daughter relationships among two cohorts of girls aged 13/14 and aged 16/17. It will seek to understand, from fathers’ and daughters’ perspectives, fathers’ influences on girls’ lives in the domains of education, work and career aspirations. In addition, how their relationships change across adolescent girls’ lives will also be explored.